The nuclear receptor co-repressor 1 is a novel cardioprotective factor against acute myocardial ischemia-reperfusion injury. (May 2022) - Qin, Zihan; Gao, Lingchen; Lin, Guanqiao; Zhu, Hong; Chen, Yingmin; Zhong, Fangyuan; Zhou, Hongmei; Duan, Shengzhong; Pu, Jun
Abstract: Acute myocardial ischemia/reperfusion (MI/R) is a major determinant of prognosis in myocardial infarction patients, while effective therapies are currently lacking. Nuclear receptor co-repressor 1 (NCoR1) is emerging as a critical regulator of cell survival and death signaling in mammals. However, the role of NCoR1 in the pathogenesis of acute MI/R injury remains unknown. Here, we observed that NCoR1 was highly expressed in the mouse heart and significantly downregulated after acute MI/R injury. Cardiomyocyte-specific NCoR1 deletion led to significantly increased infarct size and exacerbated cardiac dysfunction compared to wild-type littermates. Moreover, cardiomyocyte-specific NCoR1 deficiency exacerbated MI/R-induced mitochondrial dysfunction and apoptotic pathway activation. Transcriptomic profiling results indicated that cardiomyocyte-specific NCoR1 deficiency pivotally promoted activation of inflammatory pathways. Through integrated omics analysis, signal transducer and activator of transcription 1 (STAT1) was identified as a downstream target trans-repressed by NCoR1. STAT1 activation played a key mediating role in the detrimental effects of NCoR1 deficiency in MI/R injury. Collectively, our findings provided the first evidence that cardiomyocyte-expressed NCoR1 functioned as a crucial cardioprotective factor against acute MI/R injury by targeting the STAT1 pathway in heart. Graphical abstract: Unlabelled Image Highlights: NCoR1 expression was downregulated in heart tissues in response to ischemia reperfusion. Cardiomyocyte-specific NCoR1 deletion augmented myocardial reperfusion injury via upregulation of a NCoR1 target gene  Stat1 . The results broaden our understanding of NCoR1 roles, and provided a new potential target for treating ischemic heart injury.